Which obesity index is the best predictor for high cardiovascular disease risk in middle-aged and elderly population?. (September 2018) - Chang, Kai-Ting; Chen, Chih-Hao; Chuang, Hai-Hua; Tsao, Yu-Chung; Lin, Yan-An; Lin, Pu; Chen, Yun-Hung; Yeh, Wei-Chung; Tzeng, I-Shiang; Chen, Jau-Yuan
Highlights: VFR and WC were more strongly associated with high CVD risk than BMI among middle-aged and elderly persons. Abdominal obesity indices like VFR and WC are stronger predictors than BMI of predicting high CVD risk. The cut-off points of VFR and WC indicating high CVD risk are 12.5 and 82.50 cm for male; 7.5 and 80.75 cm for female. Abstract: Background and aims: The aim was to investigate the relationships between visceral fat rating scale (VFR), waist circumference (WC), body mass index (BMI) and cardiovascular disease (CVD) risk. Methods: In this cross-sectional, community-based study, participants completed questionnaire that included personal and medical history, and underwent anthropometric measurement and blood sampling. The 2008 general CVD risk model was used to predict CVD risk. Associations between CVD risk and VFR, WC, BMI were evaluated by means of analysis of covariance (ANCOVA) with gender as covariate, Chi-squared test, Pearson's correlation, Cochran-Armitage test, multivariate logistic regression and receiver operating characteristic curves. Results: A total of 377 people were enrolled. A significant association was identified between VFR, WC, BMI, and CVD risk, with coefficient of determination (r 2 ) of 0.32 (p < 0.001), 0.18 (p < 0.001) and 0.03 (p = 0.001), respectively. There was a trend toward increasing prevalence of high CVD risk as VFR, WC, and BMI increased (all p values <0.05). Multivariate logistic regression revealed VFR (OR = 1.21; 95%CI = 1.02–1.24), WC (OR = 1.07; 95%CI = 1.04–1.11) and BMI (OR = 1.11; 95%CI = 1.02–1.21) to be independent predictors of high CVD risk. In male, the area under curves of VFR and WC are greater than BMI: 0.641, 0.647 and 0.562. In female, the area under curves of VFR and WC are also greater than BMI: 0.656, 0.688 and 0.601. Conclusions: VFR and WC were more strongly associated with high CVD risk than BMI among middle-aged and elderly persons in Taiwan.